Measuring anti-HLA antibody active concentration and affinity by surface plasmon resonance: Comparison with the luminex single antigen flow beads and T-cell flow cytometry crossmatch results. (April 2019) - Visentin, Jonathan; Leu, Damien Le; Mulder, Arend; Jambon, Frédéric; Badier, Laure; Lee, Jar-How; Guidicelli, Gwendaline; Bouthemy, Charlène; Ralazamahaleo, Mamy; Claas, Frans; Di Primo, Carmelo; Taupin, Jean-Luc
Highlights: Active concentration and affinity of anti-HLA mAbs were determined by SPR. MAbs active concentration differed from total protein or IgG concentrations. Using active concentration for determining affinity was more accurate. SPR results were partially correlated with clinical assays. MAbs affinities were associated with the composition of their cognate epitopes. Abstract: Background: Although the Luminex single antigen flow beads (SAFB) and the flow cytometry crossmatch (FCXM) are the most sensitive assays used for anti-HLA antibodies characterization in transplant recipients, their semi-quantitative fluorescence read-out is not closely linked to graft outcome. Methods: Surface plasmon resonance (SPR) was implemented to determine truly quantitative parameters of five human monoclonal anti-class I HLA antibodies (mAbs): first the active concentration and then the binding constants. The results were compared to those obtained with SAFB and T-cell FCXM (T-FCXM). Results: The five mAbs displayed different rate and equilibrium constants for their cognate antigens. No correlation was evidenced between SAFB MFI or T-FCXM ratio and the binding parameters measured by SPR. Some mAbs amino acid substitutions within the epitope that influenced SAFB MFI resulted in affinity variations evidenced by SPR. Conclusion: The SAFB MFI and T-FCXM ratio, both semi-quantitative parameters, only partially reflected the subtlety of the anti-HLA antibody/antigen interaction as it can be analyzed by SPR. Future clinical studies using SPR for anti-HLA antibodies characterization could bring novel insights into the understanding of HLA/anti-HLA interaction and therefore anti-HLA antibodies pathogenicity.